Trillium govanianum (Himalayan Trillium): production, distribution, use and conservation in Nepal. (17th November 2021) - Thapa, Santosh; Kunwar, Ripu Mardhan; Adhikari, Binaya; Paudel, Hem Raj; Subedi, Suresh
Abstract : Trillium govanianum is known to be used for primary health care and household economy, however detailed information on its ecology and importance for local economy has remained unknown. In this study, we investigated T. govanianum population, production and distribution range, as well as its use, trade and vulnerability in Nepal. We show that the current practice of T. govanianum rhizome marketing has resulted in unsustainable harvesting, putting in extreme pressure on its habitats and populations. Harvesting methods such as premature harvesting and mass collections, without knowing actual population size and distribution, may have serious negative effects on reproduction, growth and survival of the species. To gather data and information, we sampled 80 quadrats and 320 (1 × 1 m) nested plots along with 96 interviews. Information on species occurrence points was gathered from various sources including direct field sampling and predicted potential suitable habitat using a maximum entropy model (MaxEnt). Rapid vulnerability assessment (RVA) was used to assess the conservation status of the species. Our results showed that T. govanianum occurs in 26 districts of Nepal and can be expected in 10 more mountainous districts along the elevation range between 2400 m and 4050 m. Among the environmental factors, elevation, precipitation and temperature were found to be the most influential for the species' distribution. Market‐led unsustainable collections were prevalent and T. govanianum collections were traded as an adulterant to Paris polyphylla, a highly traded medicinal plant. We found that T. govanianum is a vulnerable species with threat category I. Therefore, conservation efforts are urgently needed, including protection of its key sites and habitats along with sustainable use so as to save its existence.